Development of Basketball Learning Media in Video Form for Class X Students of SMA Negeri 7 Seluma - Bogy Restu Ilahi; Septian Raibowo; Defliyanto Defliyanto; Chintia Agustin (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The aimed of this research to develop a learning media for high school students in the form of basketball learning media in the form of videos for class X students of SMA Negeri 7 Seluma. The development model used  are the development model r&d which includes: (1) potential and problems, (2) data collection (3) doing product design (design), (4) product development (development), (5) implementation (implementation), (6) product evaluation (evaluation). The data analysis used were quantitative and qualitative which were obtained from the results of distributing questionnaires. For small group trials using a trial instrument in the form of a questionnaire given to 13 students of Ipa 2 at SMA Negeri 7 Seluma by random sampling. The product developed obtained results for the product feasibility test, namely a percentage of (80%) was obtained "very valid" and a large group trial using a questionnaire given to 32 students of Ipa 2 at SMA Negeri 7 Seluma. The product developed was obtained by product feasibility test results, namely a percentage of (84%) very valid. All the criteria have met product eligibility so that the product Development of basketball learning media in the video form in the class X SMA Negeri 7 Seluma can be used as media learning and alternative learning resources for students.